Sodium benzoate as aluminium corrosion inhibitor in acidic media / Abdul Hady Abu Bakar - Abu Bakar, Abdul Hady (Faculty of Applied Sciences, 2008)
Two different experimental methods are used in order to confirm the ability of sodium benzoate to inhibit the corrosion on aluminium in diluted sulfuric acid and diluted hydrochloride acid. The inhibition efficiency and corrosion rate of sodium benzoate is determined using polarization method and weight loss measurement. Sodium benzoate behaved as cathodic corrosion inhibitor and mixed corrosion inhibitor in diluted sulfuric acid and diluted hydrochloride acid respectively. Both results from polarization method and weight loss measurement showed that the highest inhibition efficiency was achieved at concentration of 800ppm of sodium benzoate.